Blood libel: the ritual murder accusation at the limit of Jewish history - Johnson, Hannah R. (The Univ. of Michigan Press, 2012)
The ethical dimensions of historical interpretation; the blood libel as limit case -- Thomas of Monmouth and the juridical discourse of ritual murder -- Moralization and method in Gavin Langmuir's history of antisemitism -- On being implicated: Israel Yuval and the new history of medieval Jewish-Christian relations -- Beyond implication: the Ariel Toaff affair and the question of complicity